Incidence and predictors of thyroid gland invasion by laryngeal carcinoma: a 7-year experience review - Ahmad M. Eltelety; Ahmed A. Nassar; Ahmed M. El Batawi; Sherif G. Ibrahim (The Egyptian Journal of Otolaryngology, 2020)
Abstract Background Study the incidence of thyroid gland invasion by laryngeal carcinoma and the risk factors that may predispose to this condition. Aiding surgeons develop an evidence-based plan for the management of the thyroid gland during total laryngectomy. Results Retrospective analysis of the available medical records for patients who had total laryngectomy together with total thyroidectomy or hemithyroidectomy in the same procedure. Associated pathological features were also investigated. Patients who had laryngeal carcinoma managed by total laryngectomy with total thyroidectomy or hemithyroidectomy between January 1, 2011, and December 31, 2017. Three hundred seventy-seven records were retrieved. The incidence of thyroid gland invasion by the laryngeal carcinoma was 24 (6.4%). Three patients showed microscopic extension (3/356; 0.8%). Six patients had malignant pathology other than squamous cell carcinoma (SCC). Two over six had invasion of the thyroid gland; OR (95% CI): 7.9 (1.4-45.4). Patients who had primary tumor stage of T4a were 244. 23/244 had thyroid gland invasion, 13.7 (1.8-102.9). Poorly differentiated tumors had significant incidence of thyroid gland invasion (4/15), 6.2 (1.8-21.3). Patients who had subglottic extension by the primary tumor were 177 with 20 patients having thyroid gland invasion (20/177), 6.2 (2.1-18.6). Conclusion Several risk factors are associated with higher incidence of invasion of the thyroid gland by laryngeal carcinoma. Identification of these factors can help surgeons develop a surgical strategy for the management of the thyroid gland during total laryngectomy.